Elementos Socioculturales como factores de riesgo de Trastornos Hipertensivos del Embarazo. Hospital Carlos Andrade Marín. Enero-Junio 2018 - Silva Conde, Carmen Liseth (2019)
Worldwide, hypertensive disorders are one of the most common complications of pregnancy and are responsible for a significant percentage of maternal and perinatal morbidity and mortality, especially in low-income areas. (Rojas, 2016, page 79) Objectives To establish common sociocultural factors in our environment and determine its prevalence in patients who developed hypertensive disorders in pregnancy within the established study period. Material and methods This research will be carried out at the Carlos Andrade Marín Hospital in the period from January 1, 2018 to June 30, 2018, with a retrospective and cross-sectional approach, since several socio-cultural parameters will be evaluated. in pregnant women who had hypertensive disorders to later analyze the prevalence of this problem. In the research, the empirical-analytical method will be used since the information will be synthesized through the matrix of data obtained, and by means of inclusion and exclusion criteria, pregnant women with hypertensive disorders will be taken as a population, thus excluding the rest of the population. pregnant women who have entered the Carlos Andrade Marín Hospital in the period from January 1, 2018 to June 30, 2018. Results It was found that of the 133 patients included in our study sample, 61, 6% were overweight or obesity before pregnancy, 100% have a socioeconomic status between medium / low, 96.9% are of mixed race, 96.2% reside in the city of Quito and 61.6% have been victims of violence either physical or psychological. Conclusions The Ecuadorian state in general, and specifically the city of Quito, has a well-established prevalence of each of the proposed factors for the analysis. That is to say, the positive associations between the pre-gestational weight, socioeconomic status of the patients, their ethnicity, their place of residence, being a victim of physical or psychological violence and the development of hypertensive pathologies, favor or sustain the proposed problem since in each of the variables analyzed, the prevailing statistical percentage points to a strong relationship between their presence and the development of comorbidities such as the one studied.